Multimodal conduct in the law : language, gesture, and materiality in legal interaction - Matoesian, Gregory M.; Gilbert, Kristin Enola (Cambridge : Cambridge University Press, 2018)
The study of language and law has seen explosive growth in the past twenty-five years. Research on police interrogations, trial examination, jury deliberation, plea bargains, same sex marriage, to name a few, has shown the central role of written and oral forms of language in the construction of legal meaning. However, there is another side of language that has rarely been analyzed in legal settings: the role of gesture and how it integrates with language in the law. This is the first book-length investigation of language and multimodal conduct in the law. Using audio-video tapes from a famous rape trial, Matoesian and Gilbert examine legal identity and impression management in the sociocultural performance of precedent, expert testimony, closing argument, exhibits, reported speech and trial examination. Drawing on insights from Jakobson and Silverstein, the authors show how the poetic function inheres not only in language but multimodal conduct generally. Their analysis opens up new empirical territory for both forensic linguistics and gesture studies.
Title from publisher's bibliographic system (viewed on 11 Dec 2018).
Keywords: Law -- Language; Semantics (Law); Sociological jurisprudence